Cytotoxicity and topoisomerase I/II inhibition activity of novel 4-aryl/alkyl-1-(piperidin-4-yl)-carbonylthiosemicarbazides and 4-benzoylthiosemicarbazides. (April 2014) - Siwek, Agata; Bielawska, Anna; Maciorkowska, Elzbieta; Lepiarczyk, Monika; Bielawski, Krzysztof; Trotsko, Nazar; Wujec, Monika
Abstract A series of eight thiosemicarbazide derivatives was examined for cytotoxicity in breast cancer cell cultures. Among them, 4-benzoylthiosemicarbazides proved to be only slightly less potent than chlorambucil in both MDA-MB-231 and MCF-7 lines. In contrast, 4-aryl/alkylthiosemicarbazides revealed significantly lower cytotoxicity effect. Subsequently, all titled compounds were tested as potential human topoisomerase I and II (topo I and topo II) inhibitors. Mechanistic studies revealed that tested thiosemicarbazides act as both topoisomerase I and topoisomerase II inhibitors. Among them, the best inhibitory activity was found for 4-benzoylthiosemicarbazides (1 and 2) with IC50 at 50 µM against topo II.